Rita Renoir: Quando Artaud fa lo striptease - Tomasino, Renato (Mimesis Journal, 2019)
Emotionally engaged as Stanislavskij, cruel as Artaud, Rita elaborates her strip along four ‘perversions’ of the itinerary from Eros to Thanatos: Exhibitionism formulates its double in the Icon; Nymphomania makes an obsessed repetition of it; Humiliation publicly humiliates that nymphomaniac inclination; finally, Disintegration disfigures the Icon in the corps morcelé, manifesting together the sublime exterior and the interior excrementitious and unclean. But not so much that the Simulacrum cannot return to shine, to start again...